2020
DOI: 10.1177/1746197920971808
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing service learning partnership: A human development perspective of community members

Abstract: Service–learning has, arguably, gained significant currency as a pedagogical and engagement mechanism within the broader discourse of universities and their role in community development. However, less emphasis has been placed on the human development dimensions of service–learning for community members, with the focus largely being on students’ experiential learning and other academic outcomes for the university. Though usually conceived as an integral part in university–community partnerships, community memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The results of this study are in line with other studies that found that service learning has positive effects on participants (Folgueiras et al, 2020; Mitchell, 2015; Stukas et al, 2016). Nonetheless, Mtawa and Fongwa (2022) warn that higher education institutions that provide service learning programs should be aware of power relations and that the needs and voices of beneficiary communities and organizations should be taken into account. Otherwise, service learning may become exploitative, using the beneficiaries’ needs and knowledge as resources for their students’ learning, without adequately responding to host communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with other studies that found that service learning has positive effects on participants (Folgueiras et al, 2020; Mitchell, 2015; Stukas et al, 2016). Nonetheless, Mtawa and Fongwa (2022) warn that higher education institutions that provide service learning programs should be aware of power relations and that the needs and voices of beneficiary communities and organizations should be taken into account. Otherwise, service learning may become exploitative, using the beneficiaries’ needs and knowledge as resources for their students’ learning, without adequately responding to host communities.…”
Section: Discussionmentioning
confidence: 99%
“…Service learning is a pedagogical method that combines community service with students’ accumulation of practical experience, reflection, and academic learning (cf. Bhargava and Jerome, 2020; Birdwell et al, 2013; Folgueiras et al, 2020; Mtawa and Fongwa, 2022). It is located on a continuum between internship and volunteering (Salam et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…involves intentionally linking service activities with the academic curriculum to address real community needs while students learn through active engagement and reflection". There has been S-L growth in recent business education research [10][11][12][13][14], especially in the discipline of marketing inquiries [7,[15][16][17]. The discipline of marketing is suitably compatible with S-L pedagogy because SMMEs and NPOs (non-profit organizations) frequently require marketing services but are unable to procure such services due to no or limited funds [2,17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, S-L mostly targets NPOs since these organizations mainly depend on volunteers and donations to attain their objectives. Though, there has been rapid growth in the use of S-LPs to assist SMMEs both internationally [7,10,14] and locally [13,18,19] in recent years. Market research, business and marketing plan development, marketing materials, and tools, which include advertising/MC campaigns, social media, and websites to increase sales and customers, are examples of typical marketing-related S-LPs for SMMEs [8,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation